Antiproliferative Effect of Crude Venom from Conus virgo on Human Lung Cancer Cell Line and Toxicity Assessment on Adult Zebra Fish (Danio rerio) - Ganesan, Dhana Sekaran; Mohamed, Mohamed Asik Raj; Lhanzin, Pema; Neelan, Kathirvel; Vadakkuvaselvi, Lakshmanan; Subramani, Sellamuthu; Chinnasamy, Arulvasu (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: For the past two decades, few conotoxins entered in clinical trial and some are available for pain relieving as well as for treatment of neurological disorders. Aim: The present investigation was made to elucidate the antiproliferative effect of crude venom from Conus virgo against human lung adenocarcinoma cells. Acute toxicity was determined on adult Zebra fish. Methods: Cytotoxicity was assessed by MTT assay where the DNA damage was carried out by DNA fragmentation method and the in vivo toxicity was assessed by OECD guidelines. Results: The cell viability was found to decrease and the cell lost their morphological integrity with increasing concentration (10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 μg/ml) with an IC50 concentration of 74.69 μg/ml. The nuclear integrity and DNA fragmentation assay revealed the induction of DNA damage which was observed at 5 h. Further acute toxicity study was made, the LD50 was found at a concentration of 96.393μg/ml. The crude venom affects the locomotory activity of adult Zebra fish and induces the paralytic activity at 50, 75, 100 and 125 μg/ml concentrations. Histology of brain tissue indicated slight variations in the pallium. Conclusion: From the investigation, it was inferred that C. virgo venom could be a potential candidate for cancer chemotherapy.
Keywords: A549; Conus virgo; Cone snail; Zebra fish; Acute toxicity